2019
DOI: 10.1016/j.omtm.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Retroviral Vector Integrations Away from Transcriptional Start Sites via DNA-Binding Protein Domain Insertion into Integrase

Abstract: The unique ability of retroviruses to integrate genes into host genomes is of great value for long-term expression in gene therapy, but only when integrations occur at safe genomic sites. To reap the benefit of using retroviruses without severe detrimental effects, we developed several murine leukemia virus (MLV)-based gammaretroviral vectors with safer integration patterns by perturbing the structure of the integrase via insertion of DNA-binding zinc-finger domains (ZFDs) into an internal position of the enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Our results indicate that removing the TP was insufficient to redirect all integrations away from active promoters and strong enhancers, or to eliminate the stochastic events that can select for oncogenic activation. Ultimately, a modified vector that combines SIN LTRs to eliminate strong viral enhancers [10,81] with insertions/replacement of the IN TPto redirect integration to less active regions [39,82] could decrease vector genotoxicity and overcome current limitations for clinical applications.…”
Section: In Tp-vectors For Gene Therapymentioning
confidence: 99%
“…Our results indicate that removing the TP was insufficient to redirect all integrations away from active promoters and strong enhancers, or to eliminate the stochastic events that can select for oncogenic activation. Ultimately, a modified vector that combines SIN LTRs to eliminate strong viral enhancers [10,81] with insertions/replacement of the IN TPto redirect integration to less active regions [39,82] could decrease vector genotoxicity and overcome current limitations for clinical applications.…”
Section: In Tp-vectors For Gene Therapymentioning
confidence: 99%
“…2). About 2-4 times as many BrdU + cells were seen in the ipsilateral cortex and striatum 24 (Fig. 2).…”
Section: Proliferation and Migration Patterns Of Brdu-labeled Endogenmentioning
confidence: 90%
“…Retrovirus vector particles encod-ing GFP or NeuroD1/GFP were collected from the supernatants of human embryonic kidney 293T cells and concentrated to about 10 8 TU/mL by ultracentrifugation. 24 The virus stock solution was injected into each lateral ventricle of mice being subjected to HI, and the brains were processed as described above. The expressions of GFP and NeuroD1 gene products were detected by rabbit or mouse anti-GFP (1:100; Thermo Fisher Scientific, Waltham, MA, USA) and mouse anti-NeuroD1 (1:500; Abcam, Cambridge, MA, USA) antibodies, respectively.…”
Section: Injection Of Retrovirus and Detectionmentioning
confidence: 99%
“…Next, the linearly amplified single‐stranded virus‐cell junction DNAs were filled to be double‐stranded DNA (dsDNA) with dNTP, random hexamer, and Klenow enzyme. The synthesized dsDNA products were digested with Mse I (NEB) and ligated to preannealed double‐stranded linker (linker+: 5′‐GTAATACGACTCACTATAGGGCTCCGCTTAAGGGAC‐3′, linker−: 5′‐TAGTCCCTTAGCGGAG‐NH 2 ‐3′) as described previously (Jang et al, 2019; Nam et al, 2019). The linker‐ligated virus‐cell genome junctions were finally amplified by PCR using two primers binding to the linker and 3′‐LTR of the viral genome (forward, 5′‐GACTTGTGGTCTCGCTGTTCCTTGG‐3′, and reverse, 5′‐GTAATACGACTCACTATAGGGCTCCGCTTAAG‐3′), respectively, and Phusion high‐fidelity polymerase (NEB).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we found a few internal sites within MLV integrase, where foreign proteins can be introduced without abrogating the viral infectivity (Lim, Klimczak, Yu, & Schaffer, 2010). In the following study, we showed that structural changes of MLV integrase by insertion of zinc finger domains (ZFDs) into the internal sites of the integrase could result in safer integration patterns (Nam et al, 2019). Some mutant vectors with ZFDs did not have an integration preference for the TSS regions.…”
Section: Introductionmentioning
confidence: 99%